Design and immunological evaluation of two-component protein nanoparticle vaccines for East Coast fever - Lacasta, Anna; Kim, H.C.; Kepl, E.; Gachogo, Rachael; Chege, Naomi; Ojuok, Rose; Muriuki, Charity; Mwalimu, Stephen; Touboul, G.; Stiber, A.; Poole, Elizabeth J.; Ndiwa, Nicholas N.; et al. (Frontiers Media, 2023)
Nanoparticle vaccines usually prime stronger immune responses than soluble antigens. Within this class of subunit vaccines, the recent development of computationally designed self-assembling two-component protein nanoparticle scaffolds provides a powerful and versatile platform for displaying multiple copies of one or more antigens. Here we report the generation of three different nanoparticle immunogens displaying 60 copies of p67C, an 80 amino acid polypeptide from a candidate vaccine antigen of Theileria parva, and their immunogenicity in cattle. p67C is a truncation of p67, the major surface protein of the sporozoite stage of T. parva, an apicomplexan parasite that causes an often-fatal bovine disease called East Coast fever (ECF) in sub-Saharan Africa. Compared to I32-19 and I32-28, we found that I53-50 nanoparticle scaffolds displaying p67C had the best biophysical characteristics. p67C-I53-50 also outperformed the other two nanoparticles in stimulating p67C-specific IgG1 and IgG2 antibodies and CD4+ T-cell responses, as well as sporozoite neutralizing capacity. In experimental cattle vaccine trials, p67C-I53-50 induced significant immunity to ECF, suggesting that the I53-50 scaffold is a promising candidate for developing novel nanoparticle vaccines. To our knowledge this is the first application of computationally designed nanoparticles to the development of livestock vaccines.